2009
DOI: 10.1007/s10584-009-9583-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a WRF dynamical downscaling simulation over California

Abstract: This paper presents results from a 40 year Weather Research and Forecasting (WRF) based dynamical downscaling experiment performed at 12 km horizontal grid spacing, centered on the state of California, and forced by a 1 • × 1.25 • finite-volume current-climate Community Climate System Model ver. 3 (CCSM3) simulation. In-depth comparisons between modeled and observed regional-average precipitation, 2 m temperature, and snowpack are performed. The regional model reproduces the spatial distribution of precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
173
3
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(200 citation statements)
references
References 48 publications
(64 reference statements)
15
173
3
1
Order By: Relevance
“…She compared the daytime maximum WRF SATs against California Irrigation Management Information System (CIMIS) station data and found typical errors of 3-4 K. Valade (2009) also showed that the nighttime minimum SATs are much better simulated than the maximum SATs by WRF, consistent with data in KK2007a and KK2007b where the daily mean values are more accurate than the maximum temperature values. Caldwell et al (2009) downscale NCAR CCSM finite volume (1 9 1.25°) simulations and remark that maximum temperature bias is smaller than minimum temperature while stating that daily average summer SATs are 'several degrees' K higher than observed. Soong et al (2006) compare WRF and MM5 (the Pennsylvania State University/NCAR mesoscale model version 5; Grell et al 1994) simulations during an ozone pollution event: 31 July to 2 August, 2000.…”
Section: Resultsmentioning
confidence: 97%
“…She compared the daytime maximum WRF SATs against California Irrigation Management Information System (CIMIS) station data and found typical errors of 3-4 K. Valade (2009) also showed that the nighttime minimum SATs are much better simulated than the maximum SATs by WRF, consistent with data in KK2007a and KK2007b where the daily mean values are more accurate than the maximum temperature values. Caldwell et al (2009) downscale NCAR CCSM finite volume (1 9 1.25°) simulations and remark that maximum temperature bias is smaller than minimum temperature while stating that daily average summer SATs are 'several degrees' K higher than observed. Soong et al (2006) compare WRF and MM5 (the Pennsylvania State University/NCAR mesoscale model version 5; Grell et al 1994) simulations during an ozone pollution event: 31 July to 2 August, 2000.…”
Section: Resultsmentioning
confidence: 97%
“…Caldwell et al, 2009;Chin et al, 2010;Smith et al, 2010;Dulière et al, 2011). Since the focus of this study is on dry conditions, we tested two additional configurations.…”
Section: Methodsology: Model Configurationmentioning
confidence: 99%
“…This lack of convergence is problematic because climate change impact studies often require climatic information at the small scales characteristic of, for example, a single watershed (Kanamitsu and Kanamaru, 2007;Caldwell et al, 2009). High-resolution climate model simulations are a seemingly obvious way to provide climatic information at these scales, but non-convergent behavior (e.g., extreme precipitation that systematically increases with increasing resolution) complicates interpretation of climate change studies (Li et al, 2011a,b).…”
Section: Introductionmentioning
confidence: 99%